Calibration of non‐catching precipitation measurement instruments: A review. (25th May 2021) - Lanza, L. G.; Merlone, A.; Cauteruccio, A.; Chinchella, E.; Stagnaro, M.; Dobre, M.; Garcia Izquierdo, M. C.; Nielsen, J.; Kjeldsen, H.; Roulet, Y. A.; Coppa, G.; Musacchio, C.; et al.
Abstract: Non‐catching type gauges are the emerging class of in situ precipitation measurement instruments. For these instruments, rigorous testing and calibration are more challenging than for traditional gauges. Hydrometeors characteristics like particle size, shape, fall velocity and density must be reproduced in a controlled environment to provide the reference precipitation, instead of the equivalent water flow used for catching‐type gauges. They are generally calibrated by the manufacturers using internal procedures developed for the specific technology employed. No agreed methodology exists, and the adopted procedures are rarely traceable to internationally recognized standards. The EURAMET project 18NRM03 'INCIPIT' on 'Calibration and accuracy of non‐catching instruments to measure liquid/solid atmospheric precipitation', funded by the European Metrology Programme for Innovation and Research (EMPIR), was initiated in 2019 to investigate calibration and accuracy issues of non‐catching measuring instruments used for liquid/solid atmospheric precipitation measurement. A survey of the existing models of non‐catching type instruments was initially performed and this paper provides an overview and a description of their working principles and the adopted calibration procedures. Both literature works and technical manuals disclosed by manufacturers are summarized and discussed, while current limitations and metrological requirements are identified. Abstract : Non‐catching type gauges are the emerging class of in situ precipitation measurement instruments. For these instruments, no agreed testing and calibration methodology exists, and the adopted procedures are rarely traceable to internationally recognized standards. In the framework of the EURAMET project 'INCIPIT – Calibration and accuracy of non‐catching instruments to measure liquid/solid atmospheric precipitation', this paper provides an overview and a description of existing models' working principles and the adopted calibration procedures. Both literature works and technical manuals disclosed by manufacturers are summarized and discussed, while current limitations and metrological requirements are identified.